The Effect of Supervision, Motivation Andwork Commitment with Employee Performance at Directorate General of Islamic Community Guidance Ministry of Religion of The Republic Of Indonesia - Aliyati; Supriyati, Yetty; Akbar, Ma’ruf (IJHCM (International Journal of Human Capital Management), 2020)
The objective of the research is to find out the effect of supervision, motivation, andwork commitment to the employee performance at DirektoratJenderalBimbinganMasyarakat Islam Kementerian Agama Republik Indonesia.Survey was applied in this study which data have been analyzed by path analysis after all variables put into correlation matrix and multiple regression. In this research, the employee have been chosen as a unit analysis and 150 samples selected randomly. The results of the study found that employee performance was directly influenced by supervision, motivation, and work commitment. And indirectly, employee performance is influenced by the supervisory variable and the motivation variable through work commitment, this shows that the commitment variable is not a good mediating variable. Based on these findings, it can be concluded that the variation of Supervision, Motivation and Commitment each has an effect on employee performance, but the motivation variable is more dominant in influencing employee performance, for that it is suggested to the leadership element that to improve employee motivation performance becomes a benchmark in the success of organizational performance. . The objective of the research is to find out the effect of supervision, motivation, andwork commitment to the employee performance at DirektoratJenderalBimbinganMasyarakat Islam Kementerian Agama Republik Indonesia.Survey was applied in this study which data have been analyzed by path analysis after all variables put into correlation matrix and multiple regression. In this research, the employee have been chosen as a unit analysis and 150 samples selected randomly. The results of the study found that employee performance was directly influenced by supervision, motivation, and work commitment. And indirectly, employee performance is influenced by the supervisory variable and the motivation variable through work commitment, this shows that the commitment variable is not a good mediating variable. Based on these findings, it can be concluded that the variation of Supervision, Motivation and Commitment each has an effect on employee performance, but the motivation variable is more dominant in influencing employee performance, for that it is suggested to the leadership element that to improve employee motivation performance becomes a benchmark in the success of organizational performance.